2021
DOI: 10.1371/journal.pone.0248405
|View full text |Cite
|
Sign up to set email alerts
|

Genomic variants from RNA-seq for goats resistant or susceptible to gastrointestinal nematode infection

Abstract: Gastrointestinal nematodes (GIN) are an important constraint in small ruminant production. Genetic selection for resistant animals is a potential sustainable control strategy. Advances in molecular genetics have led to the identification of several molecular genetic markers associated with genes affecting economic relevant traits. In this study, the variants in the genome of Creole goats resistant or susceptible to GIN were discovered from RNA-sequencing. We identified SNPs, insertions and deletions that disti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Moreover, we recently identified genomic variants between resistant and susceptible goats to GIN, in 78% of genes controlling the T-cell receptor-signaling pathway (32). The T-cell receptor-signaling pathway would play a role in the development of host immunity against GIN infection.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we recently identified genomic variants between resistant and susceptible goats to GIN, in 78% of genes controlling the T-cell receptor-signaling pathway (32). The T-cell receptor-signaling pathway would play a role in the development of host immunity against GIN infection.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, the resistance or susceptibility of Creole goats to gastrointestinal nematodes was studied by RNAseq (Aboshady et al, 2021). Aboshady et al (2021) reported that the T-cell receptor signaling pathway was one of the top significant pathways that distinguish the resistant from the susceptible genotype, with 78% of the genes involved in this pathway showing genomic variants in Creole goats. This shows another important example of applying omics for selecting diseaseresistant animals.…”
Section: Transcriptomicsmentioning
confidence: 99%
“…Aboshady identified variants in the GIN-sensitive or GIN-resistant creole goat genome by RNA seq, and the T-cell receptor signaling pathway was one of the most important pathways to distinguish the resistant from the susceptible genotypes, with 78% of the genes in this pathway showing a genomic variation. These genomic variants are expected to provide a useful resource for the molecular breeding of GIN resistance in goats [ 10 ]. Liu performed a comprehensive transcriptome and proteome analysis of goat skin at 45, 108 and 365 days of age, and found that the KRT and collagen α family proteins may play an important role in the development of the goat hair follicle and wool bending, providing a theoretical basis for revealing the molecular mechanism of goat wool bending [ 11 ].…”
Section: Introductionmentioning
confidence: 99%